A influência da dança sobre a flexibilidade e massa corpórea em pessoas com doença de Parkinson - SILVA, Larissa Rocha da (2024)
Parkinson's disease is increasingly common in the elderly and arises due to the degeneration of brain cells, specifically in the region called substantia nigra and ends up affecting the elderly physically and psychologically. The most common physical symptoms are tremor, stiffness, slow movement, difficulty maintaining balance and posture, affecting flexibility, the percentage of lean mass and causing a greater chance of the patient falling. Therefore, the work aims to analyze whether dance classes improve flexibility and analyze whether there was a difference in the body composition of patients. The sit and reach test was used to assess flexibility and the bioimpedance scale was used to assess the patients' body composition. The research was developed in the Baila Parkinson project, the students were divided into two groups, one made up of students who already participated in dance activities twice a week lasting one hour of class and the other group made up of participants new to the project Baila Parkinson, both underwent clinical evaluations. Significant differences were observed with increased flexibility of the lower limbs observed in elderly people already participating in dance activities. These data suggest that dancing can improve the physical condition of people with Parkinson's, with increased flexibility, which is indirectly related to reducing the risk of falls.